Analytic solutions of the chiral nonlinear schrÃ¶dinger equations investigated by an efficient approach - M. Abdul Al Woadud, K.; Kumar, Dipankar; Jahirul Islam, Md.; Imrul Kayes, Md.; Kumar Joardar, Atish (International Journal of Physical Research, 2019)
This paper studies the chiral nonlinear SchrÃ¶dinger equations, describing a central role in the developments of quantum me-chanics, particularly in the field of quantum Hall effect, where chiral excitations are known to appear. More precisely, in this paper, we acquired new exact solutions of the chiral nonlinear (1+1) and (1+2)-dimensional SchrÃ¶dinger equations by using the modified Kudraysov method. As outcomes, some of the new exact traveling wave solutions for the equations above is formally produced. All solutions are plotted in the view of three-dimensional (3D) and two-dimensional (2D) line shape through the MATLAB software for investigating the real significance of the studied equations. The periodic type of solitons is generated by employing modified Kudryashov method which is different from other studied methods.Â